New antiviral agents for the treatment of hepatitis C: ABT-450. (April 2014) - Carrion, Andres F; Gutierrez, Julio; Martin, Paul
<x xml:space="preserve">Abstract</x> Introduction: Hepatitis C virus (HCV) therapy continues to evolve rapidly. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=ABT-450&logicalOpe1=OR&field2=articletitle&text2=ABT-450&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">ABT-450 is a novel potent inhibitor of the non-structural 3/4A protease that has been studied in combination with several agents, allowing shorter duration of therapy and interferon-free/ribavirin-free all-oral regimens. Preliminary data from studies evaluating these new regimens are impressive with sustained virological response (SVR) rates of 88 – 100% after 12 weeks of therapy in patients with previously untreated HCV genotype 1 infection. SVR rates in treatment-experienced patients are also encouraging. Areas covered: Efficacy and tolerability of antiviral regimens containing ABT-450 boosted with ritonavir (ABT-450/r). Results from published studies and abstracts from recent meetings are presented. Expert opinion: Newer direct-acting antiviral agents such as ABT-450 promise effective and durable suppression of HCV with interferon/ribavirin-free all-oral regimens. This agent also allows for shorter duration of treatment and has tolerable side effects. Results of clinical trials including a broader spectrum of individuals with HCV infection are eagerly awaited.